Effect of Pre-Meal Metformin With or Without an Acute Exercise Bout on Postprandial Lipemic and Glycemic Responses in Metabolic Syndrome Patients: A Randomized, Open Label, Crossover Study - Jabeur Methnani PhD; Marwa Hajbelgacem PharmD; Taieb Ach MD; Faten Chaieb MD; Sana Sellami MD; Ali Bouslama PhD, PharmD; Monia Zaouali MD, PhD; Asma Omezzine PhD, PharmD; Ezdine Bouhlel PhD (SAGE Publishing, 2023)
Introduction: Both exercise and pre-meal metformin could lower postprandial glucose and lipid profiles. Aims: To explore whether pre-meal metformin administration is superior to metformin administration with the meal in reducing postprandial lipid and glucose metabolism, and whether its combination with exercise confer superior benefits in metabolic syndrome patients. Materials and Methods: In a randomized crossover design, 15 metabolic syndrome patients were assigned to 6 sequences including 3 experimental conditions: metformin administration with a test meal (met-meal), metformin administration 30 min prior to a test meal (pre-meal-met) with or without an exercise bout designed to expend 700 Kcal at 60% VO 2 peak performed the evening just before pre-meal-met condition. Only 13 participants (3 males, 10 females; age: 46 ± 9.86, HbA1c: 6.23 ± 0.36) were included in the final analysis. Results: Postprandial triglyceridemia was unaffected by any condition (all P > .05). However, both pre-meal-met (−7.1%, P = .009) and pre-meal-metx (−8.2%, P = .013) significantly reduced total cholesterol AUC with no significant differences between the two latter condition ( P = .616). Similarly, LDL-cholesterol levels were significantly lower during both pre-meal-met (−10.1%, P = .013) and pre-meal-metx (−10.7%, P = .021) compared to met-meal with no difference between latter conditions ( P = .822). Plasma glucose AUC was significantly reduced by pre-meal-metx compared to both pre-meal-met (−7.5%, P = .045) and met-meal (−8%, P = .03). Insulin AUC was significantly lower during pre-meal-metx compared to met-meal (−36.4%, P = .044). Conclusions: Metformin administration 30 minutes prior to meal seems to exert favorable effects on postprandial TC and LDL-Cholesterol levels compared to its administration with meal. Addition of one exercise bout only improved postprandial glycemia and insulinemia. Trial registry: Pan African clinical trial registry, Identifier PACTR202203690920424.